Shape drawing game using points as edges / Shaik Irfan Shaik Ahmad Nazri - Shaik Ahmad Nazri, Shaik Irfan (2018)
A shape is the form of an object or its external boundary, outline, or external surface, as opposed to other properties such as colour, texture or material composition. Children learn shapes in their early years to understand how things or objects look like with their names. In using points as the edge of a shape, children will learn on how many edges a shape type has thus, making them knowing shapes better and more exposed. The aim of this project is to teach kids learning shapes with classification according to number of edges by placing points that connects with lines into making a certain type of shapes. This project uses Construct 2 software as a platform for the application to create an understandable game. The evaluation of this project is conducted by validating a shape type as the output after the user inputs the points and then connecting them. It is not necessary to make a perfect shape as the user can move the points freely. The significance of this project is it helps to boost children’s creativity by placing points on their own to produce any type of shape.